2020
DOI: 10.1073/pnas.2008523117
|View full text |Cite
|
Sign up to set email alerts
|

A pathogenic and clonally expanded B cell transcriptome in active multiple sclerosis

Abstract: Central nervous system B cells have several potential roles in multiple sclerosis (MS): secretors of proinflammatory cytokines and chemokines, presenters of autoantigens to T cells, producers of pathogenic antibodies, and reservoirs for viruses that trigger demyelination. To interrogate these roles, single-cell RNA sequencing (scRNA-Seq) was performed on paired cerebrospinal fluid (CSF) and blood from subjects with relapsing-remitting MS (RRMS; n = 12), other neurologic diseases (ONDs; n = 1), and healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
174
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(193 citation statements)
references
References 95 publications
(106 reference statements)
19
174
0
Order By: Relevance
“…Furthermore, in the absence of TLR signaling, these cells will preferentially differentiate into PBs upon stimulation with IFN-γ and IL-21, thus representing a source of OCBs that may be unrelated to CNS autoantigens ( 204 ). This would be in line with a recent study that suggested that novel OCBs in RRMS patients result from the clonal expansion of memory and PB/PC populations in the CSF ( 84 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, in the absence of TLR signaling, these cells will preferentially differentiate into PBs upon stimulation with IFN-γ and IL-21, thus representing a source of OCBs that may be unrelated to CNS autoantigens ( 204 ). This would be in line with a recent study that suggested that novel OCBs in RRMS patients result from the clonal expansion of memory and PB/PC populations in the CSF ( 84 ).…”
Section: Discussionsupporting
confidence: 90%
“…OCBs are thought to be produced by ASCs derived from the local antigen-driven reactivation of memory B cells within the CNS, indicated by mutations highly concentrated within the CDR3 regions ( 82 ). This finding has been corroborated by other studies ( 83 , 84 ). This evidence of a CSF-restricted humoral response demonstrates that B cells participate in and potentially contribute to compartmentalized inflammation seen during later disease stages ( 85 ).…”
Section: Ms Pathogenesissupporting
confidence: 90%
“…Non-manual cluster annotation supported our cluster labeling ( Figure S1 B). We thus replicated the known composition and phenotype of hematopoietic lineages in the CSF ( Esaulova et al., 2020 ; Farhadian et al., 2018 ; Ramesh et al., 2020 ; Schafflick et al., 2020 ).…”
Section: Resultsmentioning
confidence: 56%
“…For example, while CD4 + T cells are the most abundant cell type in CSF, myeloid and B cells are reduced compared with blood ( Han et al., 2014 ; Kowarik et al., 2014 ). Applying modern technologies, such as single-cell transcriptomics to the CSF, multiplies the potential of the CSF to decipher the pathogenesis of neurological diseases ( Meyer Zu Hörste et al., 2020 ) as previously exemplified in multiple sclerosis and Alzheimer’s disease ( Gate et al., 2020 ; Ramesh et al., 2020 ; Schafflick et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, NGS of CD8+ and CD4+ T-cell receptor gene repertoires from CSF was used recently to support the diagnosis of MS [ 158 ] and to test the efficacy of treatment with autologous hematopoietic stem cell transplantation [ 159 ]. Furthermore, recently single-cell transcriptomics revealed increased transcriptional diversity in blood, and increased cell-type diversity in CSF including a higher abundance of cytotoxic phenotype T helper cells clonally expanded B cell in MS [ 160 , 161 ].…”
Section: Neuroimmunological and Neurodegenerative Disordersmentioning
confidence: 99%